2010
DOI: 10.1186/1471-2431-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of positive blood culture and deaths among neonates with suspected neonatal sepsis in a tertiary hospital, Mwanza- Tanzania

Abstract: BackgroundNeonatal sepsis is a significant cause of morbidity and mortality in neonates. Appropriate clinical diagnosis and empirical treatment in a given setting is crucial as pathogens of bacterial sepsis and antibiotic sensitivity pattern can considerably vary in different settings. This study was conducted at Bugando Medical Centre (BMC), Tanzania to determine the prevalence of neonatal sepsis, predictors of positive blood culture, deaths and antimicrobial susceptibility, thus providing essential informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

66
221
16
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(309 citation statements)
references
References 17 publications
66
221
16
6
Order By: Relevance
“…7,19,24 K. pneumoniae was the predominant pathogen, as has been reported in other studies. 9,16,21,23 Group B streptococcus was the most prevalent Gram-positive pathogen in our study, which contrasts with the findings in other published literature from low-to middleincome settings, in which the total absence of this pathogen was reported. 19,22,24 Pregnant women are not routinely screened for group B streptococcus in our setting and the isolation of group B streptococcus in our study is an indication of missed opportunities for antenatal screening.…”
Section: Pathogen Spectrumcontrasting
confidence: 57%
See 1 more Smart Citation
“…7,19,24 K. pneumoniae was the predominant pathogen, as has been reported in other studies. 9,16,21,23 Group B streptococcus was the most prevalent Gram-positive pathogen in our study, which contrasts with the findings in other published literature from low-to middleincome settings, in which the total absence of this pathogen was reported. 19,22,24 Pregnant women are not routinely screened for group B streptococcus in our setting and the isolation of group B streptococcus in our study is an indication of missed opportunities for antenatal screening.…”
Section: Pathogen Spectrumcontrasting
confidence: 57%
“…Our study and others from Africa report a higher prevalence of late-onset neonatal sepsis. 12,17,23,24 This pattern represents horizontal infection transmission, i.e. hospitalacquired infections, which are largely preventable by good infection control practices.…”
Section: Timing Of Neonatal Septicaemiamentioning
confidence: 99%
“…Similar results were observed in studies done by Aletayeb and Shrestha who showed 90 % and 100 % sensitivity towards imepenam, respectively 11,7 . In contrast to our study, Kayagne showed only 2 % sensitivity to meropenem and Shahian showed only 33 % sensitivity to imepenem 15,9 .…”
Section: Resultscontrasting
confidence: 53%
“…This was in accordance with the study by Shrestha, which showed that vancomycin was effective in 100 % isolates 7 . However, in study conducted by Kayagne vancomycin was effective against 14 % strains only while study by Shahian showed that ceftazidime was effective only in 22% 15,9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation